An odd kind of fame : stories of Phineas Gage - Macmillan, Malcolm, 1929- (MIT Press, 2000)
"In 1848 a railway construction worker named Phineas Gage suffered an accident ... : an explosion [that] caused a tamping iron to be blown completely through his head, destroying the left frontal lobe of his brain. Gage survived the accident and remained in reasonable physical health for another eleven years. But his behavior changed markedly after the injury, and his case is considered to be the firstto reveal the relation between the brain and complex personality characteristics."--Jacket